A Study of Women Entrepreneurship in Kanpur District - Kesari, Dr. Nidhi (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
However, the rise of female entrepreneurship has been established for many years and is generally good for job seekers, not job seekers. The relative proportion of women among total female entrepreneurs in India is one tenth. Kanpur is a large part of the Uttar Pradesh female population. The socio-economic characteristics of respondents now show that women's participation in education and training in social awareness has increased. Women entrepreneurs will promote the transfer of services in the commercial and industrial sectors. And it plays a positive role in the economy. Today, the development of women entrepreneurs in the region is not afraid, and can be encouraging and optimistic. Keywords: enterprising, socio-economic, disadvantaged women, financial support